1995
DOI: 10.1002/jlb.58.6.683
|View full text |Cite
|
Sign up to set email alerts
|

Not only Th2 cells but also Th1 and Th0 cells express CD30 after activation

Abstract: To investigate whether the CD30 molecule, expressed only by a minority of T and B cells, defines a subtype of T helper cells, Pityrosporum orbiculare-specific CD4+ T cell clones were assessed for CD30 protein and gene expression. The clones were defined as Th1, Th0, and Th2 according to their cytokine mRNA profile detected by reverse transcription PCR (RT-PCR). The kinetics of CD30 expression after OKT3 (anti-CD3) stimulation was analyzed by flow cytometry, immunocytochemistry, and RT-PCR. OKT3 activation indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
31
1
1

Year Published

1997
1997
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(36 citation statements)
references
References 14 publications
3
31
1
1
Order By: Relevance
“…Among T cells, CD30 is considered to be expressed preferentially by helper T cells, especially Th2 cells. 30,31,33,39,40 In neoplastic states, CD30 is known to be expressed by transformed cells in Hodgkin lymphoma (Hodgkin and Reed-Sternberg cells), anaplastic large cell lymphoma, and embryonal carcinoma. By contrast, the CD30 ligand (CD30L/CD153) is detectable in a variety of cell types, including T cells, granulocytes, monocytes/macrophages, and a proportion of bone marrow precursor cells of various lineages.…”
Section: Cd30 In Advanced Mastocytosismentioning
confidence: 99%
“…Among T cells, CD30 is considered to be expressed preferentially by helper T cells, especially Th2 cells. 30,31,33,39,40 In neoplastic states, CD30 is known to be expressed by transformed cells in Hodgkin lymphoma (Hodgkin and Reed-Sternberg cells), anaplastic large cell lymphoma, and embryonal carcinoma. By contrast, the CD30 ligand (CD30L/CD153) is detectable in a variety of cell types, including T cells, granulocytes, monocytes/macrophages, and a proportion of bone marrow precursor cells of various lineages.…”
Section: Cd30 In Advanced Mastocytosismentioning
confidence: 99%
“…CD30 was shown to be consistently expressed on a subset of lymphocytes known as Th2 cells (16), and accordingly, CD30 expression has been associated primarily with inflammatory disorders, such as atopic dermatitis (AD), that have a Th2 profile (17)(18)(19). However, it is now clear that Th1 and Th0 lymphocytes also express CD30 (20,21), and the distinction between Th1 and Th2 disorders based on CD30 expression is not absolute. For example, CD30 + T cells have been found in lesional skin in psoriasis, a chronic inflammatory disorder of the Th1 subtype (22).…”
Section: Introductionmentioning
confidence: 99%
“…CD30L/CD30 signaling was initially thought to be involved in Th2 cell responses and Th2-associated diseases (26)(27)(28)(29). However, a number of recent studies indicated that CD30L/CD30 signaling is also linked to Th1 or regulatory T cell responses and their associated diseases (30)(31)(32)(33)(34)(35). We have recently found that CD30L/CD30 signaling executed by T cell-T cell interaction plays a novel role in Th1 and Th17 cell differentiation in vitro and in vivo (36)(37)(38).…”
mentioning
confidence: 99%